Mid-1980s distribution of tritium, 3He, 14C and 39Ar in the Greenland/ Norwegian Seas and the Nansen Basin of the Arctic Ocean - Schlosser, Peter; Bönisch, Gerhard; Kromer, Bernd; Loosli, H. Hugo; Bühler, Renedikt; Bayer, Reinhold; Bonani, Georges; Koltermann, Klaus Peter (Progress in Oceanography, 1995)
The distributions of tritium/3He, 14C and 39Ar observed in the period between 1985 and 1987 in the Greenland/Norwegian Seas and the Nansen Basin of the Arctic Ocean are presented. The data are used to outline aspects of the large-scale circulation and the exchange of deep water between the Greenland/Norwegian Seas and the Nansen Basin. Additionally, semi-quantitative estimates of mean ages of the main water masses found in these regions are obtained. Apparent tritium/3He ages of the upper waters (depth <500m) vary from close to zero in the Norwegian Current to about 15 years at the lower boundary of the Arctic halocline. The deep waters (>1,500m depth) of the Greenland/ Norwegian Seas show apparent tritium/3He ages between about 17 years in the Greenland Sea and 30 years in the Norwegian Sea. 39Ar based estimates of the Nansen Basin intermediate, deep and bottom water ages are 91+26−23, 161+50−44 and 277+33−31 years for Arctic Intermediate Water (AIW), Eurasian Basin Deep Water (EBDW) and Eurasian Basin Bottom Water (EBBW), respectively. Within the errors, age estimates of EBDW and EBBW based on 14C/tritium correlations are consistent with those derived from 39Ar (163 to 287 years for EBDW and 244 to 368 years for EBBW). A quantitative evaluation of the data in terms of deep water formation and exchange rates based on box model calculations is presented in an accompanying paper.